2021
DOI: 10.1088/1757-899x/1055/1/012100
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Technique to Improve the Performance of Antipodal Vivaldi Antenna for Microwave Imaging Application

Abstract: A highly directional Ultra-wideband (UWB) Vivaldi antenna is offered for the study of microwave imaging utilization and radar based technique. In this paper, a novel Vivaldi antenna is designed which improve the directivity, gain and bandwidth parameters of the antenna. Initially the desired performance is achieved by making some changing in the exponential tapered structure. Again some modifications are made in the top of the patch by adding some corrugations in the flaring section, so better performance impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Though the antenna proposed in [24][25][26][27] is comparatively smaller than that of this work, it is observed that the fractional bandwidth of the proposed antenna is relatively larger than the fractional bandwidth reported by the authors and the gain is comparable. The size and fractional bandwidth of the proposed antenna in this work is superior to that of the reported work in [28][29][30], as shown in Table 2. Although, the proposed antenna in [31][32][33][34] possess better gain and fractional bandwidth; nonetheless, with larger size, more expensive substrate, and worse group delay property.…”
Section: Resultsmentioning
confidence: 62%
“…Though the antenna proposed in [24][25][26][27] is comparatively smaller than that of this work, it is observed that the fractional bandwidth of the proposed antenna is relatively larger than the fractional bandwidth reported by the authors and the gain is comparable. The size and fractional bandwidth of the proposed antenna in this work is superior to that of the reported work in [28][29][30], as shown in Table 2. Although, the proposed antenna in [31][32][33][34] possess better gain and fractional bandwidth; nonetheless, with larger size, more expensive substrate, and worse group delay property.…”
Section: Resultsmentioning
confidence: 62%
“…This result indicates a better impedance match for this antenna, resulting in less power being reflected to the source. These results underscore that this antenna is a more efficient and high-performing choice for its intended application [15,28,30].…”
Section: Results and Discussion Analysis Of S11mentioning
confidence: 64%
“…Where 𝑥(𝑡) is a function used to horizontally position the line adjusted to equations (1 & 2), and 𝑦(𝑡) is used for vertical positioning in Equations (1 & 2). Additionally, t itself is a function that adds or subtracts lines in accordance with the equations provided [15]. The optimization of the AVA design involves specific parameters aimed at achieving a wide output bandwidth, high gain, and effective radiation direction during characterization tests and tests using phantom objects [16,17].…”
Section: Designmentioning
confidence: 99%
“…An exponential slot AVA was designed in Guo et al 10 and Paul et al 11 However, the bandwidth was discontinuous after slotting. Similarly, AVAs with corrugations for microwave imaging, 12 AVA with several rectangular slots for radar, 13 an AVA with corrugations and elliptical-shaped slots for microwave and millimeter-wave applications, 14 an AVA with petal-shaped slots, 15 a VA with electromagnetic band gap slots, 16 asymmetrically slotted AVA, 17 VA with quarteroval narrow slits, 18 AVA with single semicircular slot, 19 and a palm tree-shaped VA 20 were proposed to enable. Another way to improve the bandwidth characteristics is to load resistors, such as AVAs in Xie et al 21 and Zhao et al 22 The antennas mentioned above mainly improve the loss characteristics.…”
Section: Introductionmentioning
confidence: 99%